(untitled) (Research, Society and Development, 2021)
The present work aims to demonstrate that, in the themes of prehistoric sociability and sexuality, scenes that are found in several archaeological sites around the world also occur in the existing sites in the Serra da Capivara National Park (PNSC), in Piauí, Brazil. In this way, we selected birth scenes; anthropomorphs without and with sexual differentiation, through the presence of an itiphallic stick and signs that refer to the vagina; of sexual relations currently designated as heterosexual and homosexual, including the possibility of a record of female homosexuality; bestiality; and, finally, sociability mediated either by violence or by the collective spirit. This work is part of new theoretical and methodological approaches to cultural studies, such as Gender and Queer Archeology, which subvert the traditional assumptions of archaeological science, in a manner of tensing the way in which it has contributed to the maintenance of gender binarism and dimorphic sexualities. In this sense, understanding the functioning and structure of sexual and social practices in ancestral societies contributes to comprehending these relationships nowadays. The methodology of this work consists of bibliographic and field research, in order to locate in the PNSC rock scenes related to the researched themes.